Long-Term Outcomes of Three-Dimensional High-Dose-Rate Brachytherapy for Locally Recurrent Early T-Stage Nasopharyngeal Carcinoma - Lin, Yanzhu; Ouyang, Yi; Lu, Zhiyuan; Liu, Yonghong; Chen, Kai; Cao, Xinping (Frontiers in Oncology, 2019)
Background: Brachytherapy (BT) is one of the techniques available for retreatment of patients with locally recurrent nasopharyngeal carcinoma (rNPC). In this study, we evaluated the treatment outcome and late toxicities of three-dimensional high-dose-rate brachytherapy (3D-HDR-BT) for patients with locally rNPC. Materials and Methods: This is a retrospective study involving 36 patients with histologically confirmed rNPC from 2004–2011. Of the 36 patients, 17 underwent combined-modality treatment (CMT) consisting of external beam radiotherapy (EBRT) followed by 3D-HDR-BT, while the other 19 underwent 3D-HDR-BT alone. The median dose of EBRT for the CMT group was 60 (range, 50–66) Gy, with an additional median dose of BT of 16 (range, 9–20) Gy. The median dose for the BT group was 32 (range, 20–36) Gy. The measured treatment outcomes were the 5- and 10-year locoregional recurrence-free survival (LRFS), disease-free survival (DFS), overall survival (OS) and late toxicities. Results: The median age at recurrence was 44.5 years. The median follow-up period was 70 (range, 6–142) months. The 5-year LRFS, DFS, and OS for the entire patient group were 75.4%, 55.6%, and 74.3%, respectively, while the 10-year LRFS, DFS, and OS for the entire patient group were 75.4%, 44.2%, and 53.7%, respectively. The 10-year LRFS in the CMT group was higher than that in the 3D-HDR-BT-alone group (93.8% vs. 58.8%, HR:7.595, 95%CI: 1.233-61.826, p = 0.025). No grade 4 late radiotherapy-induced toxicities were observed. Conclusions: 3D-HDR-BT achieves favorable clinical outcomes with mild late toxicity in patients with locally rNPC.